2011
DOI: 10.1016/j.brainres.2011.08.038
|View full text |Cite
|
Sign up to set email alerts
|

High novelty-seeking predicts aggression and gene expression differences within defined serotonergic cell groups

Abstract: Aggression frequently coincides with specific dimensions of emotionality, such as impulsivity, risk-taking, and drug abuse. Serotonergic (5-HTergic) neurotransmission contributes to the regulation of numerous neurobiological functions, and is thought to play a key role in modulating aggressive responses. The current study uses selectively-bred High (bHR) and Low (bLR) Responder rats that exhibit differences in emotionality and behavioral control, with bHRs exhibiting heightened novelty-induced exploration, imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
80
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 49 publications
2
80
1
Order By: Relevance
“…Interestingly, these fibers ascend just alongside the HAA [82]. These fibers contain 5-HT (serotonin) and activation of 5-HT 1A/B or 5-HT 2A/C receptors in the brain has strong modulatory but mainly inhibitory effects on aggression [56,[102][103][104][105]. To what extent this serotonergic influence is effectuated directly on HAAneurons or indirectly via the PFC and/or other brain areas, remains open for future research (see also the Neurochemistry/pharmacology section below).…”
Section: Afferent Connectionsmentioning
confidence: 98%
“…Interestingly, these fibers ascend just alongside the HAA [82]. These fibers contain 5-HT (serotonin) and activation of 5-HT 1A/B or 5-HT 2A/C receptors in the brain has strong modulatory but mainly inhibitory effects on aggression [56,[102][103][104][105]. To what extent this serotonergic influence is effectuated directly on HAAneurons or indirectly via the PFC and/or other brain areas, remains open for future research (see also the Neurochemistry/pharmacology section below).…”
Section: Afferent Connectionsmentioning
confidence: 98%
“…21-23). Relative to bLRs, bHRs are more impulsive (19), more aggressive (20), and more likely to signtrack to food-and drug-associated cues (19). Although we have previously shown that these selectively bred rats also differ in their initial propensity to take cocaine (24), the present study assesses individual differences in cocaine addiction liability by exposing bHR and bLR rats to a prolonged self-administration procedure ( Fig.…”
mentioning
confidence: 89%
“…particular, bHR rats exhibit a constellation of traits relevant to addiction (18)(19)(20) that are not necessarily apparent in outbred HR rats (e.g., refs. 21-23).…”
mentioning
confidence: 99%
“…MDMA has a unique pharmacology which, unlike that of other drugs of abuse, preferentially enhances synaptic 5-HT when administered acutely [76]. Although the novelty response has been attributed to DAergic mechanisms [77], serotonin has also been shown to play a role in the response to novelty-seeking [33,78]. High novelty-seeking appears to be a risk factor for drug addiction in general, as it tends to increase the risk of early experimentation with drugs and seems to modulate long-term MDMA-induced effects in adulthood.…”
Section: Discussionmentioning
confidence: 98%